Anti-immigration Agenda of Populist Parties in Switzerland - E. P. Shavlay; M. I. Sigachev; E. S. Sleptsov (Vestnik MGIMO-Universiteta)
The article analyzes the problem of right-wing populism in Switzerland. The study of the features of the country's political and electoral system highlights the issues of its immigration policy and relations with the European Union. The authors argue that the phenomenon of Swiss populism should be considered in a broader context, in connection with which attention is paid not only to the Swiss people's party, the Ticino League and the Geneva citizens ' Movement, but also to the populist parties of countries belonging to the Alpine macroregion – the Austrian freedom party (Austria) and the League (Italy). A discursive analysis of the programs shows that the anti-immigrant program is an essential part of the identity of right-wing populists. All of them are opposed to European integration and globalization, linking them to increased ethnic and religious tensions, unemployment and increased crime. At the same time, a special feature of Swiss parties is the fact that they position migration as a phenomenon mainly associated with cross-border movement of European citizens. Already complex, during the COVID-19 pandemic, this issue has become even more acute, and has become an integral part of their agenda. Meanwhile, the 2015-2018 migration crisis that preceded the pandemic allowed the Swiss people's party to strengthen its identity as a right-wing populist neoliberal party with a strong localist and conservative program aimed at cultural dominance over migrants. The authors also note that the Germanic focus on environmental protection is part of the populist agenda of right-wing regional parties, although it is usually characteristic of the left parties.